2014
DOI: 10.1016/j.brainres.2014.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Neurogranin binds α-synuclein in the human superior temporal cortex and interaction is decreased in Parkinson’s disease

Abstract: Neurogranin is a calmodulin binding protein that has been implicated in learning and memory, long-term potentiation and synaptic plasticity. Neurons expressing neurogranin in the cortex degenerate in late stages of Parkinson’s disease with widespread α-synuclein pathology. While analyzing neurogranin gene expression levels through rtPCR in brains of mouse models overexpressing human α-synuclein, we found levels were elevated 2.5 times when compared to nontransgenic animals. Immunohistochemistry in the cortex r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 50 publications
(69 reference statements)
2
10
0
Order By: Relevance
“…The present study finds strong correlations between α‐syn and Ng. This may be in line with the physical interaction between α‐syn and Ng observed in a small neuropathological study on PD and DLB patients . The investigators suggested that α‐syn interaction with Ng is important for synaptic function and decreased during onset of PDD .…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The present study finds strong correlations between α‐syn and Ng. This may be in line with the physical interaction between α‐syn and Ng observed in a small neuropathological study on PD and DLB patients . The investigators suggested that α‐syn interaction with Ng is important for synaptic function and decreased during onset of PDD .…”
Section: Discussionsupporting
confidence: 74%
“…This may be in line with the physical interaction between α-syn and Ng observed in a small neuropathological study on PD and DLB patients. 18 The investigators suggested that α-syn interaction with Ng is important for synaptic function and decreased during onset of PDD. 18 However, in the present study, Ng did not predict conversion to dementia in PD, nor were levels of Ng decreased in PDD compared with PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional cross-sectional studies are needed to clarify whether NGRN is specific for AD, or whether it also reflects synaptic changes in other neurodegenerative diseases. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Importantly, various studies have shown disruptions in the occipital and temporal regions in association with motor and non-motor symptoms. For example, immunoprecipitation studies have confirmed reduced neurogranin levels, in addition to the decreased interaction between α-synuclein and neurogranin in the temporal cortex in patients suffering from PD ( 11 ). Likewise, patients with PD have shown significant differences in the gray matter (GM) volume ( 12 ), and in WM underlying the temporal, and occipital cortex as compared with normal controls ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%